PERAN GURU SEBAGAI MOTIVATOR UNTUK PESERTA DIDIK - Sinarsih Sinarsih, Eva Ayu, Firda (BASA Journal of Language & Literature, 2021)
Teachers are the most important factor for students when the learning process takes place, because student learning outcomes will be more optimal if motivation is shown directly to students. Motivation has a function to encourage students to be able to select what has been done or will be done by students, also to encourage students to achieve a good achievement, motivation also functions as a director and mobilizer. The role of the teacher is very influential to grow the management of students, namely as a driver so that student learning outcomes can run smoothly and optimally. As mentioned above, the role of the teacher is as a motivator. The teacher is an inspiration who will help and fulfill the wishes and needs of students. To motivate student learning in the teaching process, teachers should not only use one monotonous learning method such as lectures or taking notes that can cause students to lose enthusiasm and get bored quickly in receiving learning. The teacher's responsibility is to help students maximize the potential of their own students and those around them. The potential learners to be nurtured not only concern intellectual issues and skills, but it involves all aspects of personality. Teachers not only need a deep understanding or ability to learn and learning can also motivate students.